Differences in long-term sedation agents used for the critically ill patients - Zein, Ahmed Ragab; Albishi, Shahad Saad; Alotaibi, Turki Nasser; Almanasif, Hidayah Dhiyaa; Qashgry, Mohammad Ibraheem; Holaibi, Saad Abdullah Al; Raggam, Lujain Darwish; Albogami, Shahad Abdullah; Aljaza, Turki Salem; Dhafar, Nimah Jameel; AlAswad, Haifaa Immad Aldin (International Journal Of Community Medicine And Public Health, 2022)
Sedative agents are commonly prescribed for critically ill patients admitted to the intensive care unit (ICU). The literature has reported many indications for using sedation for critically ill patients. These include reducing and managing high intracranial pressure, resolution of ventilator dyssynchrony, and decreasing agitation or anxiety. Different medications were reported in the literature as good sedatives for critically ill patients. Although very efficacious (benzodiazepines, propofol, and dexmedetomidine), many adverse events (as bradycardia, respiratory and myocardial depression, and hypotension) were reported as potential complications. The present literature review has discussed the potential differences and patients’ outcomes after sedation with long-term modalities in the ICU. Overall, clinicians must critically consider balancing the harms and benefits of using sedatives for critically ill patients because of the potential complications encountered during these procedures. In addition, different sedatives were reported in the literature with variable efficacies and adverse events. For example, using dexmedetomidine and propofol has been more advantageous than using benzodiazepines, and some studies also favor dexmedetomidine. However, it should be noted that adverse events are still reported with all of these modalities. Therefore, the administration of long-term sedatives should follow a strict protocol to enhance patients’ outcomes.